2014
DOI: 10.1002/app.40846
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive behavior assessment of poly(acrylic acid)‐graphene oxide composite hydrogel in the detection of cadmium

Abstract: Super absorbent polymers of acrylic acid-graphene oxide (PAA-GO) were synthesized with different percentage of chemical neutralization (0, 10, and 20%) of the acrylic acid monomer before its polymerization. The influence of their swelling and adsorption/desorption capacity of cadmium ions in aqueous solutions were studied and revealed that the GO enables greater mechanical stability in the materials. The PAA hydrogels, with the same degrees of neutralization, were also prepared without GO to compare with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In addition, a new intense peak at 1540 cm −1 was assigned to the ionized carboxylate groups (COO − ). The ionization of carboxylate groups in partially neutralized PAA has also been reported, where the H + ions of carboxylic groups in the backbone chains are irreversibly replaced by Na + . In the present study, the cationic ions are provided by ZnO‐Zn 2+ in the acidic medium during the polymerization, resulting in conditions of partial neutralization.…”
Section: Resultsmentioning
confidence: 50%
“…In addition, a new intense peak at 1540 cm −1 was assigned to the ionized carboxylate groups (COO − ). The ionization of carboxylate groups in partially neutralized PAA has also been reported, where the H + ions of carboxylic groups in the backbone chains are irreversibly replaced by Na + . In the present study, the cationic ions are provided by ZnO‐Zn 2+ in the acidic medium during the polymerization, resulting in conditions of partial neutralization.…”
Section: Resultsmentioning
confidence: 50%
“…The CPEs were prepared according to the methodology used by Bejarano-Jimenez et al [ 32 ]. The dried PAA-co-IA/NaOH and PAA-co-IA/NaOH/B-MWCNT polymers were crushed to pass through a <150 mm sieve.…”
Section: Methodsmentioning
confidence: 99%
“…The absorption of Cu(II), Zn(II), Ni(II), Co(II), Cd(II), Pb(II), and Hg(II) ions was evaluated with PAA-co-IA hydrogels, where it was determined that the degree of swelling was proportional to the content of itaconic acid [ 31 ]. In a previous work of the group, it was demonstrated that NaOH hydrogel neutralizing was a key factor in swelling as well as in its ability to remove rust in metallic surfaces [ 32 ]. In this effort, a novel synthesis of PAA-co-IA/NaOH/B-MWCNT hydrogel was developed for potential use as an electrode modifier of Cd(II) sensing carbon paste electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…By addition of chemical cross‐linker, the mechanical properties can be increased obviously. There are many reports to demonstrate polymer–graphene hydrogels such as PAM–GO hydrogel, PAA–GO, and PNIPAM–GO hydrogel by using chemical cross‐linkers.…”
Section: The Preparation Of Polymer–graphene Hydrogelsmentioning
confidence: 99%